Socio-demographic factors related to periodontal status and tooth loss of pregnant women in Mbale district, Uganda - Okullo Isaac; Engebretsen Ingunn MS; Wandera Margaret; Tumwine James K; Åstrøm Anne N (BMC, 2009)
Abstract Background Information on the socio-behavioral distribution of periodontal status and tooth loss in pregnancy emanating from sub Saharan Africa is sparse. This study examined periodontal status and tooth loss in pregnant Ugandan women and assessed the relationship with socio-demographics factors, parity, dental care and oral hygiene. Methods Mothers were participants of a multicentre cluster-randomized behavioral intervention study (PROMISE-EBF Safety and Efficacy of Exclusive Breast feeding Promotion in the Era of HIV in Sub-Saharan Africa). In Uganda, these were pregnant women resident in Mbale district, recruited into the PROMISE EBF study between January 2006 and June 2008. A total of 886 women were eligible to participate of whom information became available for 877 (participation rate 98.9%, mean age 25.6) women who participated in the recruitment interview and 713 (mean age 25.5) women who got a clinical oral examination. Periodontal status was assessed using the Community Periodontal Index of Treatment Needs (CPITN). Results The prevalence of tooth loss was 35.7%, 0.6% presented with pockets shallow pockets (4-5 mm), whereas 3.3% and 63.4% displayed bleeding and calculus, respectively. A total of 32.7% were without any sign of periodontal disease. Binary logistic regression analyses revealed that older women, women from larger households and those presenting with microbial plaque were respectively, 3.4, 1.4 and 2.5 times more likely to have CPI score >0. Rural (OR = 0.9), nulliparous (OR = 0.4) and women who never visited a dentist (OR = 0.04) were less likely, whereas women from larger households (OR = 1.5) were more likely to have lost at least one tooth. Conclusion The results revealed moderate prevalence of bleeding and tooth loss, high prevalence of calculus, low frequency of pockets 4-5 mm. Disparity in pregnant women's oral health related to parity suggests that education of maternity care providers concerning oral health in pregnancy is warranted. Trial registration ClinicalTrials.gov Identifier NCT00397150